The Impact Study of El Niño-Southern Oscillation to the Wind and Solar Data in Malaysia Using the Wavelet Analysis - Albani, Aliashim; Ibrahim, Mohd Zamri; Abdul Ghani, Siti Syazwani; Mat Rofi, Muhammad Zulkifli; Taslin, Puteri Nurfarah Adawiyah (Frontiers in Energy Research, 2021)
Malaysia has launched initiatives for utilizing renewable energy (RE) as a source of electricity since 2011 by establishing renewable energy-related laws and policies. Malaysia's geographical location and climate have led to a limited amount of intermittent RE resources. Thus, a more thorough study of the various factors affecting the RE-based electricity generation is needed for energy output optimization. This article aims to understand the impact of El Niño-Southern Oscillation (ENSO) events on wind and solar reanalysis datasets using the Wavelet Transform. The thirty-year ERA5 solar and wind datasets were used in the study, together with the multivariate ENSO Index (MEI). As a result, the selected sites experienced an increase in solar irradiation during moderate to very strong El Niño and a decrease during the La Niña period. The wind speed increases during La Niña and decreases during El Niño, with the exception of the high wind speed during the Northeast monsoon season. Also, there was a significant coherence relationship between the wind and solar datasets with the ENSO index at a specified period. Therefore, the ENSO is essential as an input factor for future development plans for wind and solar power, energy predictions, and risk assessment.